THE INFLUENCE OF JOB SATISFACTION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT THE REGIONAL DRINKING WATER COMPANY (PDAM) TIRTA JENEBERANG GOWA DISTRICT - Nailah Nurjannah; Andi Mappatompo; Sri Andayaningsih (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to analyze the influence of job satisfaction and work discipline on employee performance at PDAM Tirta Jeneberang, Gowa Regency. The research method used is quantitative with a descriptive approach. The research location was carried out at PDAM Tirta Jeneberang, Gowa Regency, over a 3 month period. Data was collected through questionnaires and analyzed using descriptive statistical methods through applicationsStatistical Package for the Social Science (SPSS) 27. The results obtained from this research show that there is a positive relationship between job satisfaction (X1) and employee performance (Y), as well as work discipline (X2) which contributes positively to employee performance (Y) at PDAM Tirta Jeneberang, Gowa Regency.